2022
DOI: 10.3390/children9020249
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Infection in Children and Infants: Current Status on Therapies and Vaccines

Abstract: Since the beginning in December 2019, the SARS-CoV-2 outbreak appeared to affect mostly the adult population, sparing the vast majority of children who only showed mild symptoms. The purpose of this investigation is to assess the status on the mechanisms that give children and infants this variation in epidemiology compared to the adult population and its impact on therapies and vaccines that are aimed towards them. A literature review, including in vitro studies, reviews, published guidelines and clinical tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 185 publications
(263 reference statements)
1
37
0
1
Order By: Relevance
“…In this study, the higher number of comorbidities and, therefore, higher CCI leads to a trend toward higher mortality (52.94% for Omicron versus 41.9% for Delta) even though it is not statistically significant, probably due to the restricted sample size; this pattern is, on the one hand, in line with data from other studies in the last two years that have shown that pre-existing comorbidities represent independent risk factors associated with COVID-19 in-hospital mortality [ 31 , 32 , 33 , 34 , 35 ]. On the other hand, no difference in the mortality between the two groups was found by Vieillard-Baron et al However, only pneumonia and immunosuppression were considered to be comorbidities [ 15 ].…”
Section: Discussionsupporting
confidence: 84%
“…In this study, the higher number of comorbidities and, therefore, higher CCI leads to a trend toward higher mortality (52.94% for Omicron versus 41.9% for Delta) even though it is not statistically significant, probably due to the restricted sample size; this pattern is, on the one hand, in line with data from other studies in the last two years that have shown that pre-existing comorbidities represent independent risk factors associated with COVID-19 in-hospital mortality [ 31 , 32 , 33 , 34 , 35 ]. On the other hand, no difference in the mortality between the two groups was found by Vieillard-Baron et al However, only pneumonia and immunosuppression were considered to be comorbidities [ 15 ].…”
Section: Discussionsupporting
confidence: 84%
“…The onset of metabolic, cardiovascular, inflammatory, neurological, psychic, and oncological diseases is often related to dysbiotic conditions [ 26 ]. A recent study on the role of the oral microbiome, dysbiosis, and long COVID was performed by metagenomic sequencing using lingual swabs from SARS-CoV-2-infected patients [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. In the oral MB of the patients with long COVID, bacteria such as Prevotella and Villanella predominated and are known to have inflammatory activity: Villanella strains stimulate IL-6 production, while Prevotella strains activate IL-23 and IL-1 and toll-like receptor 2 [ 4 , 39 , 40 , 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pediatric COVID-19 cases only accounted for a small proportion of infection in the early stages of the COVID-19 pandemic when many countries implemented non-pharmaceutical interventions and strict containment measures [8-12]. However, the incidence rate of COVID-19 in children showed a rising trend in the epidemic countries following suspension of lockdown and school reopening [12,13]. After the large-scale epidemic in early 2020, China entered a normalization stage of prevention and control, and massive COVID-19 vaccination campaign was launched nationwide in 2021.…”
Section: Introductionmentioning
confidence: 99%
“…Pediatric COVID-19 cases only accounted for a small proportion of infection in the early stages of the COVID-19 pandemic when many countries implemented non-pharmaceutical interventions and strict containment measures [8][9][10][11][12]. However, the incidence rate of COVID-19 in children showed a rising trend in the epidemic countries following suspension of lockdown and school reopening [12,13]. After…”
Section: Introductionmentioning
confidence: 99%